2019
DOI: 10.1016/j.seizure.2019.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of ambulatory video-EEG monitoring in a ˜10,000 patient nationwide cohort

Abstract: We evaluate outcome of in-home diagnostic ambulatory video-EEG monitoring (AVEM) performed on a nationwide cohort of patients over one calendar year, and we compare our findings with outcomes of inpatient adult and pediatric VEM performed during the same year at two academic epilepsy centers. Methods: This is a retrospective cohort study. We obtained AVEM outcome data from an independent ambulatory-EEG testing facility. Inpatient VEM data from a 4-bed adult epilepsy center and an 8-bed pediatric epilepsy cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 25 publications
(37 reference statements)
8
43
0
Order By: Relevance
“…In contrast, 74% of inpatient VEEG patients were in the hospital for at least 2 days for their index VEEG. These findings are consistent with previous US data; for example, a recent retrospective cohort study by Syed et al 19 examined diagnostic VEEG monitoring among $10,000 patients in the US and found a median of 4 days for length of adult inpatient VEEG and 1 day for pediatric inpatient VEEG.…”
Section: Study Populationsupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast, 74% of inpatient VEEG patients were in the hospital for at least 2 days for their index VEEG. These findings are consistent with previous US data; for example, a recent retrospective cohort study by Syed et al 19 examined diagnostic VEEG monitoring among $10,000 patients in the US and found a median of 4 days for length of adult inpatient VEEG and 1 day for pediatric inpatient VEEG.…”
Section: Study Populationsupporting
confidence: 92%
“…Conversely, disadvantages of inpatient VEEG include the artificial environment of the hospital, access to hospitals/ neurologists may be limited or inconvenient for some patients, and the high cost of services rendered in an inpatient setting 12 . A recent retrospective cohort study by Syed et al 19 examined outcomes of in-home diagnostic video-EEG monitoring among $10,000 patients over a 1-year period and found that, although selected outcomes are similar on outpatient and inpatient monitoring, outpatient monitoring for non-urgent and non-surgical epileptic events is a useful method to evaluate paroxysmal events that may be considered when inpatient level-of-care is not medically necessary. In such patients, outpatient monitoring may potentially avoid the high-cost of inpatient monitoring and avoid other inconveniences associated with inpatient VEM.…”
Section: Product-limit Survival Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The large cohort study of aVEM reported in Seizure provides important information about the utility of aVEM on a large scale. Taken in proper context, aVEM data in the Syed et al study supports prior ambulatory EEG studies from smaller single-center datasets comprised of at most 500 patients [11] and reinforces the utility of aVEM in nonurgent diagnostic evaluation of patients with seizures as Syed et al and others suggest [4][5][6][7][8]. T feasibility of analyzing "big data" in an effort to compare types of longterm video-EEG monitoring.…”
supporting
confidence: 70%
“…In this issue of Seizure, Syed et al retrospectively analyze a huge database of reports approaching 10,000 ambulatory video-EEG monitoring (aVEM) studies across 28 states from a single independent ambulatory EEG testing facility [5]. Composite results of aVEM were subsequently compared to a cohort undergoing in-patient video-EEG at a National Association of Epilepsy Centers Level IV epilepsy center derived from a 4-bed adult unit and 8-bed pediatric unit.…”
mentioning
confidence: 99%